DETERMINATION OF HUMAN DEVELOPMENT INDEX IN PENAJAM PASER UTARA - Saputra, Aksel Ary; Juliannisa, Indri Arrafi (Universitas Galuh, 2025)
Penajam Paser Utara Regency, which has been designated as the location of the Indonesian Capital City (IKN), faces problems in increasing the Human Development Index (HDI). This study aims to determine the influence of health, education, and welfare dimension indicators directly and indirectly on HDI and economic growth. The method used is the